Avaliação quali-quantitativa do fitoplâncton presente em reservatório de sistema de aproveitamento de água pluvial para irrigação - Corrêa, Thais Helena Prado (2012)
The use of rainwater can be an effective alternative to minimize the use of water sources. Within this perspective, stormwater play a key role in planning and sustainable management of water resources as a substitute for the use of water for agricultural purposes, irrigation, residential uses such as watering flowerbed and garden, cleaning floors, sidewalks and playground and car wash. Agriculture is the major user of water in the world, according to the World Resources Institute, UN agriculture uses 70% of existing drinking water. In Brazil, 88% of drinking water is used by agriculture and 5% of Brazilian crops are irrigated and 55% of farmers use archaic methods that lose more than half of the water used. Thus, alternative techniques of water management for irrigation must be proposed and implemented to mitigate the conflicts generated by the deficiency of water considering the use of rainwater as part of a broader activity, related to the expansion of water supply. Therefore, one should consider rainwater as an alternative source to conventional sources and it should investigate the potential qualitative and quantitative agreement with the intended uses. In this work the intended use is irrigation of vegetable crops for research on sustainable agricultural management techniques were therefore investigated the existence of species of phytoplankton and physical and chemical analyzes made reservoir built in the Research Center of the city-Ipeúna-SP.